DETERMINAN FINANCIAL BEHAVIOUR PADA KELUARGA DENGAN ANAK STUNTING DI KABUPATEN KOLAKA - Agus Zul Bay; Iis Afrianty; Fitri Kumalasari (Journal Publicuho, 2023)
In the Sustainable Development Goals (SDGs), one of them is overcoming the problem of stunting. Socioeconomic conditions are a supporting factor in the level of stunting in Indonesia. The government's efforts to tackle the problem of stunting are by providing financial assistance and nutritious staple foods. These efforts will certainly be effective with good financial behaviour. This research aims to examine the level of determinants of financial behaviour. The determinants of financial behaviour that are studied in this research are the effect of financial literacy, the effect of financial attitudes and the effect of lifestyle on the financial behaviour of families with stunted children in the Wundulako Community Health Center Working Area, Kolaka Regency. This research is quantitative (explanatory research). The data analysis was carried out was measuring the structural model testing model using the Structural Equations Model (SEM) analysis technique using PLS 3.0. This research shows that financial literacy and financial attitudes have a significant positive effect on financial behaviour. However, lifestyle does not have a significant effect on financial behaviour.